The effect of transport density and gender on skin temperature and carcass and meat quality in pigs (Bioscience Journal, 2017)
Pre-slaughter handling of pigs established properly is very important, not only from the point of view of welfare, but also for the quality of meat. The aim of present research was to evaluate the effect of gender and density of pigs during their transport to the abattoir on the skin temperature and carcass and meat quality. Were used 192 (115.54 ± 6.03 kg) finishing pigs to investigate the effects of gender (barrows and gilts) and transport densities for slaughter (236, 251, and 275 kg/m²) on the skin temperature and carcass and meat quality. Average skin temperature between genders and transport densities at any point of time during pre-slaughter did not differ. Skin temperatures before unloading had the highest average value relative to all other time points, followed by immediately after unloading and remaining the same for the next 2 h. Lowest skin temperature value was registered on pigs at the pre-slaughter time followed by farm and at loading times. Pigs transported with different densities did not show differences for the skin carcass lesions. Meat from pigs transported at 275 kg/m² presented higher frequency of red, soft, exudative (RSE) and lower of red, firm, non-exudative (RFN) classes as compared to those for other densities. Animals transported at 236 and 251 kg/m² did not differ as the frequency of RSE and RFN meat. Skin temperature of pigs oscillate along the pre-slaughter times and the pre-slaughter transport of pigs at 236 and 251 kg/m² generates less frequency classes of faulty pork, although difference in the densities did not have any effect on the skin temperature and skin lesions.